(untitled) - Morrow, Stephen (New York, 2003)
Soccer leagues worldwide are being dominated by clubs who are becoming richer and more powerful. Enormous corporate investment, deals with media giants, merchandising and dedicated TV channels mean that soccer teams are as concerned with the affairs of the boardroom as what is going on on the field. In this dynamic book, Stephen Morrow examines the changing face of soccer, looking at issues such as the role of the stock exchange, the stakeholder approach, the "new economics" of soccer including the role of media firms.
Keywords: Soccer,Soccer teams,Soccer; Economic aspects,Finance,Social aspects; Europe,Europe,Europe